(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The technology of today’s world are continuously change with computer, robots and machine, replacing simple human activities. Artificial intelligence is one of them innovation. Many sectors are getting benefited from this new technology but other side of this technology misused in various sector as like personal and profession. The Intellectual Property Rights (IPR) and also AI stem from the world intelligence. The copyright law of India declare states that an effort is to remain qualify aimed at copyright defence their uses to be a modicum of creativity standard. This paper disclose about AI working module, Intellect stuff right of India, copyright act in India, Indian patent Act, The design Act and privacy. Artificial Intelligence determination be playing a significant part in the development of patent law itself. AI based on Computer system, which is designed and also drafting the current industrial design protection laws and legislations may not declare to be enough provide them desired protection.